First record of the genus Tagalis Stål, 1860 (Hemiptera: Reduviidae: Saicinae) from Colombia with the description of two new species - Castro-Huertas, Valentina; Forero, Dimitri (Zootaxa, 2014)
Tagalis Stål is recorded for the first time from Colombia and two species are described as new: Tagalis dichroa sp. nov., from Acandí (Chocó), and Tagalis albispina sp. nov., from Gorgona Island (Cauca). Based on the structure of the male genitalia of the known species, we here propose at least four species groups within Tagalis: 1) T. evavilmae, 2) T. femorata, 3) T. baenai, T. grossii, and T. marquesi, and 4) T. dichroa sp. nov., T. inornata, and T. seminigra. Tagalis albispina sp. nov. known only from the female holotype, cannot be placed into this scheme. Digital micrographs of the habitus and genitalia of the new species are provided. An updated key to the species of Tagalis is presented to facilitate the identification of the new species.